2017
DOI: 10.1002/adsc.201701194
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox Catalysis in C–S Bond Construction: Recent Progress in Photo‐Catalyzed Formation of Sulfones and Sulfoxides

Abstract: The emergence of radical chemistry as well as green chemistry in organic synthesis has initiated an interest in photochemistry over the past decade. With catalytic amounts of photoredox catalysts under light irradiation, high active radical species are produced, which could trigger the subsequent organic transformations smoothly. Among the various photoredox reactions, photo‐catalytic C–S bond formation continues to thrive, as the C–S bond is indispensable in many important biological and pharmaceutical compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(65 citation statements)
references
References 145 publications
1
64
0
Order By: Relevance
“…Visible light photoredox catalysis has emerged as a powerful strategy for organic synthesis. 1 However, the development of catalytic asymmetric photoredox reactions is still highly desirable and remains a formidable challenge owing to the difficulties in controlling the stereochemistry of highly reactive intermediates such as radicals and radical ions. 2 , 3 Pioneering work by Sibi, Porter, and others has demonstrated that transition-metal-based chiral Lewis acids are capable of governing the enantioselective conjugate addition of radicals produced by stoichiometric reduction of organic halides ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Visible light photoredox catalysis has emerged as a powerful strategy for organic synthesis. 1 However, the development of catalytic asymmetric photoredox reactions is still highly desirable and remains a formidable challenge owing to the difficulties in controlling the stereochemistry of highly reactive intermediates such as radicals and radical ions. 2 , 3 Pioneering work by Sibi, Porter, and others has demonstrated that transition-metal-based chiral Lewis acids are capable of governing the enantioselective conjugate addition of radicals produced by stoichiometric reduction of organic halides ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, visible-light promoted organic synthesis has emerged as a highly economical and eco-friendly strategy for the construction of various chemical bonds under mild conditions. [94][95][96][97][98][99][100][101][102][103][104][105] Particularly, visible-light photoredox catalysis is an ideal tool to initiate radical cascade reactions for the synthesis of heterocycles. [106][107][108][109][110][111][112][113][114][115][116][117][118] In 2017, Hong's group reported a visible-light-enabled radical strategy to synthesize spiroepoxy chroman-4-one derivatives 74 via a tandem oxidation/radical cyclization/epoxidation process (Scheme 14).…”
Section: Visible-light-promoted Reactionsmentioning
confidence: 99%
“…[9][10][11] Visible light photoredox catalysis has evolved into an important method in organic chemistry and can provide superior reaction conditions. [12][13][14][15] The rst example of a photoredox thiol-yne click reaction under metal-free conditions with good yields and selectivity for b-vinylsuldes was reported in 2016. 16 Later, Wang and co-workers reported a photoredox process driven by 1 mol% mesityl-10-methyl-acridinium tetra-uoroborate, providing a range of mono-and bis-substituted sulde products.…”
Section: Introductionmentioning
confidence: 99%